Identification of Victims Who Have Experienced Advanced Decay - Sembiring, Asan Petrus (Talenta Publisher, 2022)
Background. In the process of investigating a criminal offense, knowing the identity of the victim is something that has a very important meaning, namely as an initial step of the investigation that must be made clear before the next steps can be taken in the investigation process. Objectives. to prove that the skeleton is a human skeleton, race, gender, estimated age, height. Case Illustration. Reported cases of a group of bones thought to have originated from human bones. Taken to the hospital to identify who the victim was. Discussion. Examination found a collection of 196 human bones, in the form of head, neck and the whole body remains bones as well as the right upper limb and lower limb still found skin and muscles that began to dry, blackish brown, foul smelling , a black cocoon (pupa) with a length of 3 cm, and a white maggot (instar I larvae) with a length of 0.5 cm.. Conclusion. Collection of bones derived from humans, with an estimated Mongoloid race (Asian), male sex, age 15-25 years, height 157-165 cm, duration of death 10-20 days, with signs of violence in the form of blood infiltration on the left head bone and right skull fracture that extends to the back. the cause of death of the victim is blunt trauma to the head that causes a skull fracture. Keywords: Victim Identification, Further Decay